2020
DOI: 10.1530/joe-20-0277
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal exposure to androgens dynamically alters gut microbiota architecture

Abstract: Gonadal steroids strongly contribute to the metabolic programming that shapes the susceptibility to manifestation of diseases later in life, and the affect is often sexually dimorphic. Microbiome signatures, together with metabolic traits and sex steroid levels, were analyzed at adulthood in neonatally androgenized female rats, and compared with those of control male and female rats. Exposure of female rats to high doses of androgens on early postnatal life resulted in persistent alterations of the sex steroid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 52 publications
2
12
0
Order By: Relevance
“…In contrast, increases in Lactobacillus , Lacnospiraceae NK4A136 , Eisenbergiella , Roseburia , Bacteroides , the Eubacterium xylanophilum group, and Parasutterella were reported for male and female GDX rats, Blautia and Alloprevotella for male GDX rats, and uncharacterized UCG-008 in female GDX rats. Altogether, this set of analyses confirmed and extended the previous literature data indicating sex differences in gut microbiota [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ] and the role of sex steroid hormones [ 9 , 12 , 14 , 15 , 16 ]. As described above, the gut exhibits sexual dimorphism in both its steroidogenic capability and microbial composition.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In contrast, increases in Lactobacillus , Lacnospiraceae NK4A136 , Eisenbergiella , Roseburia , Bacteroides , the Eubacterium xylanophilum group, and Parasutterella were reported for male and female GDX rats, Blautia and Alloprevotella for male GDX rats, and uncharacterized UCG-008 in female GDX rats. Altogether, this set of analyses confirmed and extended the previous literature data indicating sex differences in gut microbiota [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ] and the role of sex steroid hormones [ 9 , 12 , 14 , 15 , 16 ]. As described above, the gut exhibits sexual dimorphism in both its steroidogenic capability and microbial composition.…”
Section: Discussionsupporting
confidence: 88%
“…Among several factors which can influence the composition of the gut microbiota, sex is a major contributor [ 7 ]. Both human and animal studies, mainly performed in mice, have reported sex-related differences in the gut microbiota [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ], and a role has been proposed for sex steroid hormones in contributing to this sexual dimorphism [ 9 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. Additionally, inhibition of key enzymes in steroidogenesis, such as 5-alpha-reductase (5α-R), alters gut microbiota populations in rodents and humans [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…GLP-1 has been well established in reducing body weight and lowering blood sugar through inhibiting gastrointestinal peristalsis and gastric juice secretion and enhancing insulin secretion [ 24 ]. A variety of studies have confirmed that impaired glucose homeostasis was reflected by higher AUC of GTT and ITT [ 25 , 26 ]. Furthermore, the concentration of TG and TC in the feces of all mice was detected to confirm the regulation of metabolitin on lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“… 10 - 15 There is a bidirectional relationship between steroid hormones and gut microbial communities, 16 , 17 with studies showing that prenatal and neonatal exposure to androgens can lead to gut dysbiosis in rats. 18 - 20 Several studies have shown that women with PCOS show taxonomical differences in their gut microbiomes and further signs of dysbiosis, including a reduced α-diversity that negatively correlates with serum testosterone levels in both healthy and obese PCOS subjects. 21 - 24 Imbalances in the gut microbiome can lead to the compromise of intestinal epithelial cell connections and a “leaky” gut, increasing the permeability of the gut lining to inflammatory mediators such as lipopolysaccharides.…”
Section: Introductionmentioning
confidence: 99%